Techno-Economic Impact of Grid-Connected Rooftop Solar PV System for Schools in Palestine: A Case Study of Three Schools. - Ibrik, Imad; Hashaika, Fadia (International Journal of Energy Economics and Policy, 2019)
The application of the On-grid PV power systems is currently experiencing significant increase and expanding vastly as an alternative source of energy provider for different buildings in Palestine. In the Palestinian territories most of the electricity is provided by the neighboring countries which imposes burden on the Palestinian economy due the insecurity of the electricity supply and fluctuation in its tariff especially in the last years. Palestine is very rich in the solar resources with an annual average of 5.4 peak sun shine hours and has a great potential for PV powered projects, this paper presents a 12-month-long performance evaluation of the 7.68 kWp grid-connected PV systems on the rooftop of each of the three schools in Palestine: Al-Razi Boys School, Almueh Boys School & Khawleh Bent Al Azwar Girls. The performance of implemented PV systems show that the average performance ratio was 78 %, the average annual energy produces by each system equal 10.930 MWh/year. The results of economic analyses are encouraging to intensify the use of such PV school systems since the payback period of such a system is less than 5 years, the cost of kWh produced is around 0.1 US , the internal rate of return around 20%. Besides these results, this paper presents also the impacts of PV school systems on the electric grid represented in decreasing the losses, and raising the voltage level, and the effect of PV systems on the environment. Keywords: Photovoltaics, Grid-connected PV system, Economic feasibility, School buildings, Palestine. JEL Classification: Q24 DOI: https://doi.org/10.32479/ijeep.7593